Bibliometric study on clinical research of osteoporosis in adolescents - Li, Dingshuang; Ou, Jingxi; Zeng, Yang; Hou, Lei; Yuan, Yu; Luo, Zhiyuan (Frontiers in Public Health, 2023)
Objective Focusing on the theme of " osteoporosis-related research in adolescents, "a systematic visualization of the developmental lineage, current research status, hot spots, and trends of adolescent osteoporosis was conducted to provide a reference for subsequent related research, clinical diagnosis, and treatment. Method The Web of Science core database was used as the data source to retrieve the relevant literature and the bibliometrics method. An online bibliometric platform, CiteSpace, and VOSviewer software were used to conduct co-occurrence analysis on the authors, scientific research institutions, national cooperation, keywords, and funding sources to draw the relevant knowledge map. Result A total of 1199 publications from the Web of Science core database were included in this study. The number of published AOP studies has shown an upward trend over the past 29 years, with the United States being the major contributor to the field with the highest number of publications (291, 24.3%) and the highest number of citations (12,186). The international collaboration map shows that the United States is the country most focused on international collaborative exchanges, with the closest collaboration between the United States and Canada. The most influential research institutions and authors are Children's Hospital and Catherine M Gordon. the United States is the primary funding source for this research area. Research hotspots were mainly focused on "bone density," "osteoporosis," and "children." Conclusion These knowledge maps review the research hotpots in adolescent osteoporosis research over time, analyze and summarize the research process over the past 29 years, and predict future research directions.